2018
DOI: 10.1080/02640414.2018.1424498
|View full text |Cite
|
Sign up to set email alerts
|

Body composition, metabolism, sleep, psychological and eating patterns of overtraining syndrome: Results of the EROS study (EROS-PROFILE)

Abstract: Overtraining syndrome (OTS) is caused by an imbalance between training, nutrition and resting, and leads to decreased performance and fatigue; however, the precise underlying triggers of OTS remain unclear. This study investigated the body composition, metabolism, eating, sleeping patterns and mood states among participants with OTS. Selected participants were divided into OTS-affected athletes (OTS, n = 14), healthy athletes (ATL, n = 25), and healthy non-physically active controls (NCS, n = 12). Compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
1
5

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(92 citation statements)
references
References 28 publications
5
81
1
5
Order By: Relevance
“…Overall and consistent with our findings in the other arms of the EROS study, [15][16][17] the OTS athletes appeared more similar to sedentary individuals than to healthy athletes, reflecting relative (compared with the expected results in athletes) but not actual dysfunctions (compared with the general population). Athletes tended to have a lower hematocrit than sedentary participants, which contradicts the findings of one study 18 that revealed an increased hematocrit in OTS participants, although this was either not mentioned or no differences were observed in other studies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Overall and consistent with our findings in the other arms of the EROS study, [15][16][17] the OTS athletes appeared more similar to sedentary individuals than to healthy athletes, reflecting relative (compared with the expected results in athletes) but not actual dysfunctions (compared with the general population). Athletes tended to have a lower hematocrit than sedentary participants, which contradicts the findings of one study 18 that revealed an increased hematocrit in OTS participants, although this was either not mentioned or no differences were observed in other studies.…”
Section: Discussionsupporting
confidence: 89%
“…1,15 All 39 athletes performed both endurance and resistance activities, including the high-intensity functional training regimen CrossFit in 78.6% (11 of 14) and 96% (24 of 25) of the OTS and ATL groups, respectively. [15][16][17] The characteristics of OTS presented by the affected participants are detailed in Table 3. Given the lack of specific performance tests for diagnosing OTS, the different patterns of the tests performed by each affected athlete, and the complexity of the sports performed by all the athletes, the results of each athlete's specific tests before and during OTS are not described here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The in uence of body composition on sports has attracted people's attention. For example, body composition affects the recovery of exercise performance [14], and differences in body composition between overtraining syndrome subjects and healthy subjects [15], and relationship between athletic performance and body composition [16].…”
Section: Introductionmentioning
confidence: 99%